Profitability and Financial Performance in Islamic Commercial Banks: Testing the Role of Good Corporate Governance as a Moderating Variable - Meila Catur Arista; Zulfikar Zulfikar (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the impact of profitability on financial performance in Islamic Commercial Banks and the moderating role of Good Corporate Governance (GCG) from 2019 to 2023. Using purposive sampling, 15 banks registered with the Financial Services Authority (OJK) were analyzed based on annual reports, though data limitations due to missing or incomplete reports posed challenges. Financial performance was measured by Return on Assets (ROA), while profitability was assessed through Net Profit Margin (NPM). GCG variables included the Independent Board of Commissioners, Board of Directors, Institutional Ownership, Sharia Supervisory Board, and Audit Committee, selected for their role in maintaining financial stability and ensuring compliance with Sharia principles. The results, analyzed using multiple linear regression and Moderated Regression Analysis (MRA), indicate that profitability significantly influences financial performance. However, the Independent Board of Commissioners, Board of Directors, and Institutional Ownership did not strengthen this relationship, likely due to their advisory rather than managerial roles. In contrast, the Sharia Supervisory Board and Audit Committee enhanced the relationship, highlighting the importance of Sharia compliance and financial oversight. The study is limited by sample size and data constraints, impacting result generalizability. Future research should expand the sample and explore additional governance mechanisms unique to Islamic banking to provide deeper insights into financial performance determinants.